Analytical study of MgZnO/ZnO heterostructure field effect transistor for power switching. (19th July 2022) - Kumar, Pawan; Chaudhary, Sumit; Khan, Md Arif; Mukherjee, Shaibal
Abstract: We investigate the power switching mechanism to evaluate the power loss ( P D ) and efficiency ( ɳ ) in MgZnO/ZnO (MZO)‐based power heterostructure field effect transistor (HFET), and physical parameters responsible for P D in molecular beam epitaxy (MBE) and dual ion beam sputtering (DIBS) grown MZO HEFT and compare the performance with the group III‐nitride HFETs. This work extensively probes all physical parameters such as two‐dimensional electron gas (2DEG) density, mobility, switching frequency, and device dimension to study their impact on power switching in MZO HFET. Results suggest that the MBE and DIBS grown MZO HFET with the gate width ( W G ) of 205 and 280 mm at drain current coefficient ( k ) of 11 and 15, respectively, will achieve 99.96% and 99.95% of ɳ and 9.03 and 12.53 W of P D, respectively. Moreover, W G value for DIBS‐grown MZO HFET is observed to further reduce in the range of 112–168 mm by using a Y2 O3 spacer layer leading to the maximum ɳ in the range of 99.98%–99.97% and the minimum P D in the range of 5–7 W. This work is significant for the development of cost‐effective HFETs for power switching applications.